2021
DOI: 10.1002/adfm.202102439
|View full text |Cite
|
Sign up to set email alerts
|

Progressive NO2 Sensors with Rapid Alarm and Persistent Memory‐Type Responses for Wide‐Range Sensing Using Antimony Triselenide Nanoflakes

Abstract: Antimony triselenide (Sb 2 Se 3 ) nanoflake-based nitrogen dioxide (NO 2 ) sensors exhibit a progressive bifunctional gas-sensing performance, with a rapid alarm for hazardous highly concentrated gases, and an advanced memory-type function for low-concentration (<1 ppm) monitoring repeated under potentially fatal exposure. Rectangular and cuboid shaped Sb 2 Se 3 nanoflakes, comprising van der Waals planes with large surface areas and covalent bond planes with small areas, can rapidly detect a wide range of NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To assess the NO 2 sensing performance, we conducted a comparative analysis of InS (Table S1, ESI†) with respect to various sensors utilizing 2D semiconductors (SnS 2 , 55 Sb 2 Se 3 , 56 N-doped In 2 S 3 , 57 black phosphorus, 58 and reduced graphene oxide 59 ), graphitic carbon nitride, 60 metal oxides (In 2 O 3 nanoparticles, 61,62 and SnO 2 nanowires 63 ), and diverse heterostructures (SnO 2 /SnSe 1.7 , 64 In 2 O 3 /SnS 2 , 65 SnO 2 /SnS 2 , 66 SnSe 2 /SnO/SnSe, 67 and In 2 O 3 nanoparticles/SnO 2 nanowires 63 ). The evaluation revealed that InS outperforms state-of-the-art materials, exhibiting a superior sensing response and lower LOD than all the aforementioned systems.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the NO 2 sensing performance, we conducted a comparative analysis of InS (Table S1, ESI†) with respect to various sensors utilizing 2D semiconductors (SnS 2 , 55 Sb 2 Se 3 , 56 N-doped In 2 S 3 , 57 black phosphorus, 58 and reduced graphene oxide 59 ), graphitic carbon nitride, 60 metal oxides (In 2 O 3 nanoparticles, 61,62 and SnO 2 nanowires 63 ), and diverse heterostructures (SnO 2 /SnSe 1.7 , 64 In 2 O 3 /SnS 2 , 65 SnO 2 /SnS 2 , 66 SnSe 2 /SnO/SnSe, 67 and In 2 O 3 nanoparticles/SnO 2 nanowires 63 ). The evaluation revealed that InS outperforms state-of-the-art materials, exhibiting a superior sensing response and lower LOD than all the aforementioned systems.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the performance for NO 2 sensing, we compared α-In 2 Se 3 with other sensors based on 2D semiconductors (SnS 2 , 65 Sb 2 Se 3 , 66 N-doped In 2 S 3 , 67 black phosphorus, 68 reduced graphene oxide 69 ), graphitic carbon nitride, 70 metal oxides (In 2 O 3 nanoparticles, 71,72 SnO 2 nanowires 73 ), and various heterostructures (SnO 2 /SnSe 1.7 , 74 In 2 O 3 /SnS 2 , 75 SnO 2 /SnS 2 , 76 SnSe 2 /SnO/SnSe, 77 In 2 O 3 nanoparticles/SnO 2 nanowires 73 ). The comparative analysis highlights the superior suitability of α-In 2 Se 3 compared to state-of-the-art materials, with significantly higher sensing response and lower LOD than all other above-mentioned systems.…”
Section: Resultsmentioning
confidence: 99%
“…The values found for https://doi.org/10.26434/chemrxiv-2024-np6zg ORCID: https://orcid.org/0000-0001-7971-5567 Content not peer-reviewed by ChemRxiv. License: CC BY 4.0 𝐿𝐷𝐿 are below those reported in recent studies, and also far below the level which is considered harmful to human health [18,30,[44][45][46][47][48]. The reactivity derived from both chalcogenide elements, as well as the exposure of surface defective edges by exfoliation are considered factors that can influence the sensitivity of NO2 sensor devices.…”
Section: Gas Sensing Measurementsmentioning
confidence: 96%